Influência do manejo da água no desempenho de cultivares de arroz irrigado em várzea de Roraima - Morinigo, Emilia Estefania Villalba (2016)
The objective of this study was to determine the influence of water management on the performance of irrigated rice cultivars. For such an experiment under field conditions was conducted during the crop year 2014/15, in the White River floodplain area, savannah region, the City of Cantá, Roraima state. The experimental design was a randomized block in scheme of arrangement in tracks, with four replications. We studied the tracks, the effects of water management systems, M1: flash flood; M2 flash flood in the vegetative phase up to 50% medium bloom, followed by continuous flooding to maturity (90% of mature panicle); M3: continuous flooding in the vegetative phase to 50% flowering, followed by intermittent flooding to maturity and M4: continuous flooding throughout the cycle. The plots consisted of eight rice cultivars, established at random, BRS 358, BRS Tropical, Catiana BRS, BRS Pampa, Roraima, IRGA 424, IRGA 428 and PUITA INTA CL. We evaluated the plant height characteristics, cycle, panicles number per m2, panicle length, number of grains per panicle, 1000 grain, grain yield in kg ha-1 yield of whole grains and water consumption. Data were subjected to analysis of variance with application of F test and means were compared by the Scott-Knott test at the 5% level of significance. To assess the degree of association between the characteristics were calculated the Pearson correlation coefficients (r). It was concluded that: the performance of rice cultivars was influenced by different water management systems for the most features; there was no difference in mean grain yield between the different water management systems; the BRS and BRS Catiana Pampa were the most productive in the M1 and M2 water management systems; the BRS Catiana, IRGA 424 and IRGA 428 were the most productive in M3 water management system and BRS Catiana the M4; BRS Catiana had the highest average grain yield (8309.15 kg ha-1) considering all water management systems; the water management system M1 showed the lower consumption and greater efficiency in water use.